DeEPs a new instance-based lazy discovery and classification system. - Li, Jinyan (Machine learning.)
Distance is widely used in most lazy classification systems. Rather than using distance, we make use of the frequency of an instance's subsets of features and the frequency-change rate of the subsets among training classes to perform both knowledge discovery and classification. We name the system DeEPs. Whenever an instance is considered, DeEPs can efficiently discover those patterns contained in the instance which sharply differentiate the training classes from one to another. DeEPs can also predict a class label for the instance by compactly summarizing the frequencies of the discovered patterns based on a view to collectively maximize the discriminating power of the patterns. Many experimental results are used to evaluate the system, showing that the patterns are comprehensive and that DeEPs is accurate and scalable.